Design of a 100 Watt High Gain Cascaded Modified Boost Converter with Continuous Input Current - Mamat, Mohd Nadzri; Kaharuddin, Suardi; Abdullah, Mohamad Nazir; Ishak, Dahaman (Journal of Advanced Research Design, 2026)
The conventional boost topology can be constructed to achieve high voltage gain by employing an extreme duty cycle, which can lead to inefficiencies, heightened voltage stresses, and instability. In order to address these challenges, this study introduces a high gain cascaded modified boost converter. This converter is specifically tailored for low voltage input sources necessitating high voltage amplification, such as those found in renewable energy systems. The design offers advantages including simplified switching control, high voltage gain, consistency across a broad duty cycle range, continuous input current, and scalability for achieving further gains. The paper elaborates on the operational principles, design considerations, and specifications of this proposed converter. Validation through Simulink simulations has demonstrated that the proposed design can effectively operate within the specified parameters, delivering a well-regulated output of 96 V and 1.04 A from a 12 V input source, with minimal output ripple of less than 0.4%.